The professional competence formation of future library-information specialists under conditions of changing the training areas nomenclature of higher education (evidently for English-language training) - N. V. Lopatina; M. A. Romanyuk (Библиосфера)
The paper examines the harmonization of information-library education and a new nomenclature of training directions approved by order of the Ministry of Science and education in Russia 12.09.2013 № 1061 («On the list of specialties and fields of training of higher education approval»). This topic is related to the acutest and most relevant theoretical problem of modern library science, namely to define the essence of the library profession. The purpose of the authors is to show that the library profession place in this list is determined by the content and direction of higher education in this sphere, its competency benchmarks. The article designates gaps of librarian training in the system of cultural education and the complexity of forming the systemic view on a united information space, reveals the complex of scientific-bibliographic, scientometric competencies, professional readiness to work with certain types of information resources and categories of users, mastering modern technologies of information-library services. A special attention is paid to the English-language training of the future librarian at the university. It is proved that he should learn a foreign language not only at the level of general cultural and professional competence sufficient to communicate on professional topics. In addition it is important to have the ability for professional work with information resources, to carry out basic information processes in foreign languages. The idea of forming new competences resulting as the expansion of traditional understanding of library, overcoming the collection locality, opportunities and demand of remote access, opening Russian libraries and information centers collections, information files and flows for foreign readers is developed. The practical results of the research are forms and methods of English-language training of future librarians as information specialists.